REAGAN STAR (RS) BEST DRIVER SELECTION USING MULTI FACTOR EVALUATION PROCESS (MFEP) METHOD - Kusdanu Waskito, Saptono (Dinasti International Journal of Digital Business Management, 2021)
Reagan Star(RS) is a carpet distributor company that serves customers in Bandung Metropolitan. The number of customers served throughout Bandung Metroprolitan is 134 customers. Reagan Star has 5 (five) drivers who are used to distribute carpets in the Bandung Metropolitan area, namely Ali, Beni, Calsum, Dudi, Eman. The problem faced by Reagan Star is that the drivers have not provided individual performance as expected by Reagan Star, among others, often coming late to the Reagan Star office, late in delivering goods to customers, goods delivered to customers not in accordance with customers. This situation causes customer disappointment. Bandung Metropolitan. The leadership of Reagan Star originally had a plan to replace 5 (five) drivers with new drivers. The obstacle faced by the leadership of Reagan Star was that the old drivers had special customers who if the delivery of goods was not carried out by a certain driver, the customer would be reluctant to buy. the strategy of stopping the driver from becoming the driver of the Reagan Star, causing revenue from carpet sales to diminish. The Reagan Star leadership has a new strategy. The leadership organizes the selection of the best drivers. The Reagan Star leadership selects the best drivers using the Multi Factor Evaluation Process (MFEP) method. In selecting the best driver, the Reagan Star leadership determines 3 (three) dimensions that will be assessed for orderly traffic, quality of delivery of goods, and financial responsibility. In the first stage of unweighted assessment, the one who gets the highest score is Calsum. In the second study using the Multi Factor Evaluation Process (MFEP) where each dimension was assigned a weighted value, the results still determined Calsum as the winner. Many are orderly traffic, followed by the dimensions of the quality of delivery of goods, and finally financial responsibility. Conversely, if the assessment uses the MFEP method, the dimension that has the highest average value is orderly traffic, and the second is the financial responsibility variable and the last dimension is the quality of the delivery of goods. the driver starts from an orderly traffic, followed by good quality delivery of goods, followed by generating cash which is brought to Reagan Star. good quality of delivery of goods, resulting in cash which is a financial responsibility.